1999
DOI: 10.1007/s002130051143
|View full text |Cite
|
Sign up to set email alerts
|

A neurotoxic regimen of MDMA suppresses behavioral, thermal and neurochemical responses to subsequent MDMA administration

Abstract: It is concluded that the long-term depletion of brain 5-HT produced by MDMA is accompanied by impairments in 5-HT function, as evidenced by the deficits in the neurochemical, thermal and behavioral responses to subsequent MDMA administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
115
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(132 citation statements)
references
References 30 publications
15
115
2
Order By: Relevance
“…It was demonstrated that the increase in the extracellular concentration of ACh in the PFC elicited by MDMA was attenuated in rats previously exposed to a neurotoxic regimen of MDMA in much the same manner as has been reported for the MDMA induced increase in 5-HT release (Shankaran and Gudelsky, 1999;Shankaran et al, 2001). In contrast, physical (i.e., tail pinch) or psychological (i.e., intruder rat) stressors evoked a similar increase in ACh release in the PFC of control animals and animals previously exposed to a neurotoxic regimen of MDMA (Nair and Gudelsky, 2006b).…”
Section: Long Term Effects Of Repeated Mdma Administrationsupporting
confidence: 62%
See 1 more Smart Citation
“…It was demonstrated that the increase in the extracellular concentration of ACh in the PFC elicited by MDMA was attenuated in rats previously exposed to a neurotoxic regimen of MDMA in much the same manner as has been reported for the MDMA induced increase in 5-HT release (Shankaran and Gudelsky, 1999;Shankaran et al, 2001). In contrast, physical (i.e., tail pinch) or psychological (i.e., intruder rat) stressors evoked a similar increase in ACh release in the PFC of control animals and animals previously exposed to a neurotoxic regimen of MDMA (Nair and Gudelsky, 2006b).…”
Section: Long Term Effects Of Repeated Mdma Administrationsupporting
confidence: 62%
“…However, following a neurotoxic regimen of MDMA, the ability of a subsequent injection of MDMA to elicit the 5-HT behavioral syndrome has been shown to be greatly diminished (Shankaran and Gudelsky, 1999;Shankaran et al, 2001). Series et al (1995) and Baumann et al (1998) also have demonstrated that the acute behavioral effects of fenfluramine are diminished following treatment with 5-HT depleting regimens of p-choloramphetamine, fenfluramine or MDMA.…”
Section: Long Term Effects Of Repeated Mdma Administrationmentioning
confidence: 99%
“…A gradually diminishing temperature dysregulation in rat dams was also seen by [76]. The development of thermal tolerance is not unique to females or to pregnancy as a blunted temperature dysregulation also occurs in adolescents [118] and adults [25,142]. The mechanism(s) responsible for tolerance, especially at different ages, is presently unclear as, in addition to the activation of uncoupling proteins by norepinephrine and thyroid hormones [103], dopamine, serotonin, and several cytokines mediate the core temperature response to MDMA [58].…”
mentioning
confidence: 89%
“…A locomotor sensitization two weeks after an escalating MDMA regimen was reported [127,128]. In contrast, the serotonin syndrome and pyrexia was substantially reduced one week after a rat MDMA binge [142].Intermittent MDMA exposure every five days beginning on PD 35 (adolescence) lead to a reduction in the temperature dysregulation and headweaving stereotopy by PD 60 [118]. Prior embryonic experience modified the behavioral response to a second MDMA treatment in newly hatched chickens [13].…”
mentioning
confidence: 99%
“…Although it could be argued that the development of compensatory mechanisms diminishes the clinical importance of MDMA-induced neurotoxicity, an alternative view is that MDMA-induced lesions produce a brain milieu of diminished functional reserve that may become clinically apparent under various forms of stress. One method that has proved useful for unmasking such 'subclinical' deficits in animals treated with neurotoxic doses of MDMA has been the use of pharmacological challenge (Poland et al, 1997;Virden and Baker, 1999;Shankaran and Gudelsky, 1999;Gardani et al, 2005). The foregoing studies demonstrate that animals with MDMA-induced lesions that exhibit normal behaviors or physiology at baseline have abnormal thermal, behavioral and circadian responses to pharmacological challenges with drugs that influence these 5-HTmediated functional domains.…”
Section: Introductionmentioning
confidence: 99%